Effect of planting dates and densities on yield and yield components of short and ultra-short growth period maize (Zea mays L.) - Van Averbeke, Wim (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Agronomy))--University of Pretoria, 2007.